Elementos norteadores para gestão da produtividade: o caso de uma empresa de manufatura automotiva - Chaves, Bruna Tolino (Universidade do Vale do Rio dos Sinos, 2023)
This work proposed a set of guiding elements for productivity management with application in automotive manufacturing companies. To this end, the variables that influence productivity management were analyzed and identified in the literature. The literature search identified 82 studies compatible with the theme, and was supported by the systematic literature review as a research method. From the search, analysis and synthesis of the findings, it was possible to propose a theoretical framework, with the definition of these variables, the proposed framework was categorized according to the similarity of the subjects, creating four categories: people, method, infrastructure and material, and unfolding the variables from these. At the end, the case study methodology was applied, in order to confront the literature findings, with analyses of two automotive manufacturing cells. From this, it was possible to signal factors compatible with the literature and new factors not described in the study bases. The conclusion of this stage resulted in the fulfillment of the general objective of this work, outlining the guiding elements for productivity management. This phase also included feedback with the management of the two manufacturing cells, pointing out the coherence of the results obtained and the importance of the proposed system for productivity improvements. This study suggests that automotive manufacturing companies apply this system by means of a primer or a standard operating procedure, ensuring an analysis standard that contemplates the six variables listed in this study as priorities. This work highlights the importance of productivity management working on improvements with combined and not isolated factors, a point that is restricted in the current literature, since in most cases the factors are treated in isolation.
Keywords: Produtividade; Gestão da produtividade; Elementos da produtividade; Productivity; Productivity management; Elements of productivity; ACCNPQ::Engenharias::Engenharia de Produção